PUNCTUATION AND WRITTEN SPEECH PROBLEMS IN UZBEKI (World Bulletin of Social Sciences, 2024)
The article describes the existence of a synonymous relationship between punctuation marks in the Uzbek language, and this relationship occurs through the use of one instead of the other in the text. The method and procedure of using punctuation marks, the organic connection of punctuation marks with the syntactic structure of the language are discussed. This article shows, with examples, that there is a practice of using one punctuation mark instead of another, but using this practice does not always produce the expected result